Pengaruh Pertumbuhan Ekonomi, Pendapatan Asli Daerah Terhadap Alokasi Belanja Modal Dengan Dana Alokasi Umum Sebagai Variabel Pemoderasi Pada Kabupaten/ Kota Di Provinsi Di Sumatera Utara - Eka Sridawati Purba; Elsa Lorreinne Pradipta; Ruth Trifosa Taruli Manullang; Benny Rojeston Marnaek Nainggolan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The allocation of expenditure in the Regional Revenue and Expenditure Budget (APBD) in the form of capital expenditure aims to increase the fixed assets and the development of the region so as to create equitable development in each region, but the allocation of capital expenditure is not used productively by local governments, it can be seen from the imbalance of development between regions. The purpose of this study is to examine the effect of Economic Growth (PE), Regional Original Income (PAD) on the allocation of Capital Expenditure (BM) and General Allocation Funds (DAU) as moderating variables in Regencies / Cities in North Sumatra Province. The type of data used in this study is secondary data with multiple linear regression tests. The results of this study partially Economic Growth does not affect the allocation of Capital Expenditures, but Regional Original Revenue partially influences the allocation of Capital Expenditures. Simultaneously Economic Growth, Local Own Revenue and General Allocation Funds have positive and significant effect on capital expenditure. The General Allocation Fund moderates the effect of Economic Growth on the allocation of Capital Expenditures and the General Allocation Fund does not moderate the influence of the Local Revenue to the allocation of Capital Expenditures. Keywords: Economic Growth, Local Own Revenue, Capital Expenditures, General Allocation Funds